x2 + 8x - 9 = 0

A. 1

B. 3

C. -3

D. -9

E. -1

Another questions on Mathematics

- A scientist wants to use a model to help present the results of his...

2 - For the functions f(x)=6x2−6x+3 and g(x)=4x2+6, find (f−g)(x) and (f−g)(4)....

2 - What is the biggest difference between arma international and aiim...

1 - What was not a result of the interaction between greek city-states...

1 - Bri and annamarie are picking strawberries at two different strawberry...

2 - What skills or attributes make you a good environmental scientist...

1 - One example of a right or freedom that is protected by the bill of...

1 - 3[ 2(10-5) +5(6-5) ] =...

1 - Please write 10 sentences on what you learned about the Roman Empire....

2 - Have you ever seen a pot of water on the stove? What have you observed...

1

magdlenejekkar14.02.2022 04:10Step-by-step explanation:

Given quadratic equation is:

x² + 8x - 9 = 0

Using mid-term break formula

x² + 9x - x - 9 = 0 (When we multiply middle terms, we get side terms as answer which is mid term break formula.)

Taking common

x(x + 9) - 1(x + 9) = 0

Take (x + 9) common

(x + 9)(x - 1) = 0

According to zero's method:

Either:

x + 9 = 0 OR x - 1 = 0

x = -9 OR x = 1

Hope this helped!

~AH1807